PP89 Antioxidant activity of Ganoderma lucidum evaluated by electrochemical assays - Martínez Suárez, Jaime Fernando; Ruiz Bravo, Lisette Dyanna; Benavides Calvache, Olga Lucía (Revista Productos Naturales, 2025)
This study investigated the antioxidant activity and electrochemical behavior of the fungus G. lucidum using electrochemical techniques. Cyclic voltammetry (CV) and differential pulse voltammetry (DPV) were performed in a three-electrode system, utilizing glassy carbon as the working electrode, Ag/AgCl as the reference electrode, and a platinum rod as the auxiliary electrode, in a 0.02 M acetate buffer solution (pH 5.0). G. lucidum exhibited antioxidant activity, suggesting an electroactive chemical composition. Furthermore, the Epa for G. lucidum was more anodic with respect to the standards ascorbic acid and gallic acid